The effect of surface charges of liposomes in immunopotentiation. Issue 2 (February 1984) - Latif, Nahid; Bachhawat, Bimal K.
Abstract : The purpose of this study was to establish the effect of surface charges of liposomes on its adjuvant activity to an entrapped protein antigen. The immune responses of rabbits immunized subcutaneously with lysozyme entrapped in neutral negatively and positively charged liposomes and compared with complete Freund's adjuvant (CFA), showed positively charged liposomes to be a better adjuvant than neutral, negatively charged liposomes and even CFA. This was true for solid liposomes also. Interestingly, injection of positively charged liposomes led to the formation of granulomas at the sites of immunization, which was not observed with neutral and negatively charged liposomes.